Envisioning Intelligent Information Technologies through the Prism of Web Intelligence. - Ning Zhong; Jiming Liu; Yiyu Yao (Communications of the ACM, 2007)
The article discusses intelligent information technologies, which focus on Web intelligence, the hybridization of techniques, and distributed and parallel processing. The technique is regarded as a generational leap in information technology, which could lead to intelligent information processing through the use of artificial intelligence, pattern recognition, learning theory, and data mining. The technology could also open up new avenues of profit for businesses, which will be able to share and sell their information more easily.